Advocacy et nouveaux modes managériaux : le rôle politique de deux ordres professionnels de la santé - Mireille Lalancette; Marie-Josée Drolet; Marie-Ève Caty (Communiquer)
This article discusses the rhetoric deployed by two professional orders, the Ordre des ergothérapeutes du Québec and the Ordre des orthophonistes et des audiologistes du Québec, when they are called upon to contribute to public debates on various social issues. What rationalities do they promote and how are these rationalities are in tension with those articulated by the government? To answer this question, we analyzed 10 recent briefs tabled at the National Assembly of Quebec. Our analyses reveal four rationalities: political, economic, scientific and ethical. By revealing these rationalities, we highlight the tensions between bureaucratic and professional logic. This article thus helps to demystify a little-known political communication exercise.